Pengaruh Kepercayaan Diri dan Kecerdasan Emosional Terhadap Kemampuan Penyelesaian Soal Cerita Matematika Siswa Kelas VIII SMP Negeri 4 Baubau - Dian Lestari; Arief Mustafa Nasrudin (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2021)
Problem statement of this research was Whether there was: 1) simultaneous influence between self-confidence and emotional intelligence on ability to solve Mathematics word problem; 2) a positive and significant influence of self-confidence on ability to solve Mathematics word problem; and 3) a positive and significant influence of emotional intelligence on ability to solve Mathematics word problem of the student at VIII grade of SMP Negeri 4 Baubau. This research was quantitative research with the type of Expost Facto. Population of this research was all students at VIII grade of SMP Negeri 4 Baubau with the total number was 352 students and spread over 11 parallel classes, with the sampling in this research of 25% of the total population or as many as 88 students. Data collection technique in this research conducted by using research instrument which was questionnaire of self-confidence and emotional intelligence as well as mathematical ability tests, to measure students’ mastery of mathematical statistics material in this case the word problem in the form of probability. The data obtained were analyzed using descriptive analysis and inferential analysis, in the form of multiple linear regression analysis.Based on the results of the research, it was concluded: 1) there was a simultaneous influence of self-confidence and emotional intelligence on the ability to solve mathematics word problems of student at VIII grade of SMP Negeri 4 Baubau, this could be seen from the value of Sig. < alpha, (0.013 < 0.050); 2) partially, there was a negative effect of self-confidence on the ability to solve mathematics word problems of student at VIII grade of SMP Negeri 4 Baubau, this could be seen from the value of Sig. < alpha, (0.049 < 0.050). 3) As for testing the third hypothesis, there was a positive influence of emotional intelligence on the ability to solve mathematics word problems of student at VIII grade of SMP Negeri 4 Baubau, this could be seen from the value of Sig. < alpha, (0.017 < 0.050).